Fear of cancer recurrence in oncohematological patients: assessment instruments and evidence-based psychological interventions — a systematic review - Sancho-Martínez, Ana; Rueda-Extremera, María; Alejandre-Carmona, Sergio; Cantero-García, María (Frontiers in Psychology, 2025)
IntroductionOncohematological patients undergo a complex emotional adaptation process, in which Fear of Cancer Recurrence (FCR) is one of the most prevalent concerns. This fear not only negatively impacts their psychological well-being but is also associated with a significant reduction in quality of life.ObjectiveThis study aims to conduct a systematic review of the available evidence regarding: (1) The factors associated with FCR in oncohematological patients. (2) The validity and reliability of the instruments used for its assessment. (3) The therapeutic interventions designed to mitigate FCR in this population, with particular focus on those supported by solid empirical evidence.Methodology:A systematic review was conducted following the PRISMA guidelines. The literature search was performed in November 2024 across the PubMed, PsycINFO, Web of Science, ProQuest, SUMMON, SciELO, Redalyc, Dialnet, and Google Scholar databases. Rigorous inclusion and exclusion criteria were applied to ensure the methodological quality of the selected studies.ResultsAfter the selection process, 11 studies meeting the eligibility criteria were included. The main findings were: (a) FCR assessment instruments: Four validated tools specifically designed for oncohematological populations were identified. (b) Therapeutic interventions: Four programs based on cognitive-behavioral therapy and third-wave therapies were found to be effective in reducing FCR in patients with leukemia, lymphoma, and multiple myeloma.ConclusionThis systematic review provides a comparative evaluation of measurement methods and the most effective interventions for addressing FCR in oncohematological patients. The findings highlight the need for further research tailored to the specific characteristics of this population, fostering the development of more precise and accessible therapeutic strategies.